2016
DOI: 10.1111/gcb.13481
|View full text |Cite
|
Sign up to set email alerts
|

Species‐specific responses to climate change and community composition determine future calcification rates of Florida Keys reefs

Abstract: Anthropogenic climate change compromises reef growth as a result of increasing temperatures and ocean acidification. Scleractinian corals vary in their sensitivity to these variables, suggesting species composition will influence how reef communities respond to future climate change. Because data are lacking for many species, most studies that model future reef growth rely on uniform scleractinian calcification sensitivities to temperature and ocean acidification. To address this knowledge gap, calcification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
62
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 86 publications
9
62
4
Order By: Relevance
“…To date, studies addressing the effects of OA on coral reefs have been performed mostly at the scale of individual organisms, and have focused on calcification as a response variable (Schoepf et al, 2013;Comeau et al, 2013;Okazaki et al, 2016), while studies focusing on larger spatial scales (i.e., whole communities) have remained rare, mostly because of technical constraints (e.g., Dove et al, 2013;Comeau et al, 2015Comeau et al, , 2016b. The few experiments addressing the effects of OA on intact coral reef communities have confirmed the threat to calcification rates previously reported for individual organisms, notably by showing a decreased capacity of communities to maintain positive net calcification under conditions mimicking a future ocean in which seawater pH will be depressed 0.15-0.30 units relative to presentday conditions (e.g., Dove et al, 2013;Comeau et al, 2015Comeau et al, , 2016b.…”
Section: Introductionmentioning
confidence: 99%
“…To date, studies addressing the effects of OA on coral reefs have been performed mostly at the scale of individual organisms, and have focused on calcification as a response variable (Schoepf et al, 2013;Comeau et al, 2013;Okazaki et al, 2016), while studies focusing on larger spatial scales (i.e., whole communities) have remained rare, mostly because of technical constraints (e.g., Dove et al, 2013;Comeau et al, 2015Comeau et al, , 2016b. The few experiments addressing the effects of OA on intact coral reef communities have confirmed the threat to calcification rates previously reported for individual organisms, notably by showing a decreased capacity of communities to maintain positive net calcification under conditions mimicking a future ocean in which seawater pH will be depressed 0.15-0.30 units relative to presentday conditions (e.g., Dove et al, 2013;Comeau et al, 2015Comeau et al, , 2016b.…”
Section: Introductionmentioning
confidence: 99%
“…The Intergovernmental Panel on Climate Change (IPCC) has projected that sea surface temperatures in the Caribbean region could rise between 0.6 and 3.0 • C by the end of the twenty-first century (ocean warming), and atmospheric pCO 2 will surpass 600 µatm, causing surface ocean pH to decrease by 0.1-0.3 pH units (ocean acidification) (IPCC, 2014). These projections pose significant threats to reef-building corals throughout the Caribbean, causing mass mortality events, reducing recruitment, deteriorating key physiological processes, and lowering coral calcification rates (Jokiel and Coles, 1977;Grottoli et al, 2006;Davies et al, 2016;Okazaki et al, 2017). Despite the consensus that global change will negatively affect Caribbean reef-building corals, the extent of these impacts vary widely by species, region, or measured physiological response parameter (Harvey et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the consensus that global change will negatively affect Caribbean reef-building corals, the extent of these impacts vary widely by species, region, or measured physiological response parameter (Harvey et al, 2013). A great example of such variation in coral responses to ocean acidification and warming is seen in Okazaki et al (2017) where some species exhibited no response to ocean acidification or warming while other corals in the same experiment exhibited reduced calcification under one or both stressors. Furthermore, a study conducted by Kenkel et al (2015) demonstrated a variety of physiological responses (i.e., calcification and Symbiodiniaceae physiology) of corals under ocean warming even within a single species.…”
Section: Introductionmentioning
confidence: 99%
“…Ocean acidification (OA) has been identified as a key but understudied stressor for marine organisms, leading to rapid growth in efforts to test its effects on a wide range of potentially susceptible species (Kroeker, Kordas, Crim, & Singh, ; Kroeker et al., ). Although experiments have revealed that many species are negatively impacted by OA, some organisms exhibit mixed responses and we know less about the variation in OA response among closely related taxa or among taxa with similar physiological traits (e.g., Calosi et al., ; Dupont, Ortega‐Martínez, & Thorndyke, ; Gooding, Harley, & Tang, ; Noisette, Egilsdottir, Davoult, & Martin, ; Okazaki et al., ; Ries, Cohen, & McCorkle, ). As a consequence, it is unclear if variation in the response of species to OA is a result of inherent physiological differences among species or a result of infrequent efforts to test for generalities across taxa (Gaylord et al., ; O'Connor, Selig, Pinsky, & Altermatt, ; O'Connor et al., ; Wernberg, Smale, & Thomsen, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although experiments have revealed that many species are negatively impacted by OA, some organisms exhibit mixed responses and we know less about the variation in OA response among closely related taxa or among taxa with similar physiological traits (e.g., Calosi et al, 2013;Dupont, Ortega-Martínez, & Thorndyke, 2010;Gooding, Harley, & Tang, 2009;Noisette, Egilsdottir, Davoult, & Martin, 2013;Okazaki et al, 2017;Ries, Cohen, & McCorkle, 2009).…”
Section: Introductionmentioning
confidence: 99%